Managerial response to eWOM posted by consumers from different cultures : A case study of the hotel industry in northern Sweden - Belfrage, Marcus; Palo, Lovisa (Luleå tekniska universitet, Institutionen för ekonomi, teknik och samhälle, 2020)
Word of Mouth (WOM) is an ancient concept that has been around since the uprising of markets. However, due to the increased internet usage a new form of WOM has emerged called Electronic Word of Mouth (eWOM). The concept of eWOM takes form when consumers communicate with each other or a company online. Consumers can communicate by sharing positive and negative comments about the experiences they have had with companies and products. These comments have a positive or negative effect on consumer satisfaction and a company's reputation. Due to this it is important for companies to communicate with their consumers online across various platforms. Companies can communicate with their consumers by responding to comments. An industry that frequently responds to consumers eWOM is the hotel industry. Hotel guests often write reviews and comments online that managers in the hotel industry respond to. However, hotels have visitors from all around the world and consumers from different cultures tend to engage in eWOM in different ways. This is important for hotels to be aware of. Hence, the purpose of this study is to gain a more profound understanding on how managers in the hotel industry respond to eWOM posted on social media and review sites by consumers from different cultures. This study is a case study where two hotels located in northern Sweden have been interviewed. The interviewees of the two hotels are managers with a lot of experience of the hotel industry. The findings of the case study suggest that hotels respond to consumers' positive and negative eWOM. Positive comments are usually responded to with a personalized and appreciative response to increase consumer satisfaction. Negative comments are responded to by addressing the issue in order to make up for service failure. The study also found that hotels do not pay much attention to cultural differences and the reason for this is because most of the hotel’s consumers are from individualistic cultures.